Sertifikasi Guru: Sudah Siapkah Guru Madrasah? - Yayat Suharyat (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2006)
Basically, education is a human investment. Therefore, various components and apparatus are required to support the improvement of quality of education. One of them is teacher. As imposed in the government regulation concerning teachers and lecturers, a teacher is on condition that he should be professional and hold an adequate level of competence so that he can be expected to create high-quality students